PENGARUH LINGKUNGAN KELUARGA DAN SEKOLAH TERHADAP PERILAKU BERAGAMA SISWA DI MTs AR-RAHMAN NGLABAN - Hahan Aryahiyyah Nabilah; Suwandi (JOURNAL SAINS STUDENT RESEARCH, 2024)
The process of a person's development from childhood to adulthood is known as the adolescent phase. Teenagers experience quite high development in various things at this point. They are influenced especially in terms of religious behavior by a high level of curiosity and are very emotionally unstable. This can be influenced by their environment, especially their family and school environment. The objectives of this research are as follows: (1) determine whether the family environment influences students' religious behavior at MTs Ar-Rahman Nglaban; (2) determine whether the school environment influences students' religious behavior at MTs Ar-Rahman Nglaban; and (3) determine whether the family and school environments each influence the religious behavior of students at MTs Ar-Rahman Nglaban. This research was carried out using qualitative methods and random sampling techniques. As a sample, this research used 120 students as respondents. Data were obtained through statistical tests and multiple linear regression analysis. The results of the research are as follows: (1) the family environment significantly influences students' religious behavior, as shown by the hypothesis test (sig value 0.000 < 0.05 and Tcount result 2.194 > 1.981); H0 is rejected and Ha is accepted. (2) the school environment influences students' religious behavior significantly, as shown by hypothesis testing (significance value 0.030 < 0.05)